Digital Diasporas: Postcoloniality, Media and Affect - Ponzanesi, Sandra (Interventions (London, England), 2020)
This essay revisits the notion of diaspora in connection with recent advancements in communication technologies, which have led to the formation of 'digital diasporas'. The focus is on digital migrants as 'connected users', and therefore as participants in social media platforms. Though there is no consensus on what digital diaspora means exactly because it depends on its many disciplinary takes and media-specific variations, such as 'e-diasporas', 'digital diasporas', 'net-diasporas' and 'web-diasporas', there is consensus on the profound ways in which digital connectivity has transformed privileged terms of spatiality, belonging and self-identification. Digital diasporas provide new possible cartographies to map the self in relation to increasingly complex patterns of globalization and localization, while avoiding closures and the negative effects of identity politics. Furthermore, it allows different scripts to be envisioned for the politics of emotion that is essential to the understanding of the motives, nature and impact of the migrant experience, as well as the possibility for negotiating multiple belongings. The essay reviews some of the disciplinary or media-specific takes that have emerged from science and technology studies, media, communication studies and migration studies, anthropology and sociology. Offering a postcolonial intervention into this interdisciplinary field, the essay analyses 'digital diaspora' as a relational term that operates on three levels - Internet-specific, network-oriented and embedded in wider social practices - while also accounting for political, geographical and historical specificities.